Does a Menstrual State and Hormonal Contraception Use Determine Exercise Participation? A Study of 8060 Exercising Women - Emily Bowring; Jessica Hill; Amal Hassan; Emily Cushion; Jamie Tallent; Charles R Pedlar; Georgie Bruinvels (Journal of Physical Activity and Health, 2026)
Background : Menstrual states and hormonal contraceptive (HC) use may affect athletic training and performance. The prevalence of different menstrual states, menstrual dysfunctions, and HC use is not well established in the exercising population. This study aims to describe this, as well as identify the impact that menstrual states may have on training and performance. Methods : 8060 premenopausal women, aged 18 years or over, from 6 territories were recruited through the STRAVA™ exercise app. An online survey was completed to understand current menstrual states, HC use, current exercise volume, and perceived influence of the menstrual cycle on training and competition. Results : The most prevalent menstrual state was amenorrhea (42.1%), and HC was used in 39.7% of participants. The occurrences of oligomenorrhea (14.5%), nonhormonal IUD (NonH IUD) (6.0%), amenorrhea (4.4%), and polymenorrhea (1.1%) were comparatively lower. HC users were significantly less likely to miss/change training compared with amenorrhea ( P < .001) or polymenorrhea ( P = .035) cycles. HC users were significantly less likely to miss a race/event/competition than those with a eumenorrheic cycle ( P < .001) or amenorrhea ( P = .021). Those with polymenorrhea were significantly more likely to miss a race/event/competition than those with a eumenorrheic cycle ( P = .032), oligomenorrhea ( P < .001), HC users ( P < .001), or NonH IUD users ( P = .017). Ovarian cysts (11.3%) and polycystic ovarian syndrome (7.9%) were the most reported forms of menstrual dysfunctions. Conclusions : Most participants were eumenorrheic or using hormonal contraception. Having polymenorrhoea or amenorrhea was associated with an increased likelihood of negative outcomes on exercise participation. Those using HC were less likely to miss/change training.